The impact of ISO 9001 certification process on Slovenian companies - Marjan Pivka; Dusko Ursic (Journal for East European Management Studies, 2002)
This study aims (i) to investigate the correlation between ISO 9000 quality management system and business success based on data from certified Slovenian companies, (ii) to find out the factors for measuring efficiency of ISO 9000, and (iii) to give suggestions to all involved in the certification process. A questionnaire survey was conducted among all ISO certified companies in Slovenia (more than 600 per September 2000) in order to collect primary data. The basic conclusions, proved by statistical analysis are: (i) the influence of ISO 9000 on business success can not be explained by known benefits as for instance: better management control, improved awareness of procedural problems, improved customer service etc., and (ii) ISO 9000 will influence business success (will be efficient) when it is integrated by the company with general organization, resources management, productivity, profit and innovations, as these factors explain best the influence of ISO 9000 on business efficiency. – – Diese Studie befaßt sich (i) mit der Wechselbeziehung zwischen dem ISO 9000 Qualitätsmanagementsystem und dem Betriebserfolg, der auf Daten zugelassener slowenischer Unternehmen basiert, (ii) um die Faktoren zur Meßbarkeit der Effizienz von ISO 9000 zu finden und (iii) um Vorschläge für alle am Zulassungsprozeß Beteiligten herauszuarbeiten. Eine Umfrage wurde unter allen zugelassenen Firmen in Slowenien (mehr als 600 im September 2000) durchgeführt, um Primärdaten zu erhalten. Die grundlegenden Folgerungen, die von statistischen Analysen belegt wurden, waren: (i) Der Einfluß von ISO 9000 auf den Geschäftserfolg kann nicht durch bekannte Leistungen wie bessere Managementkontrolle, verbesserte Sensibilisierung für verfahrensorientierte Probleme, verbessertem Kundenservice etc. erklärt werden; und (ii) ISO 9000 wird den Erfolg (wird effizienter) beeinflußen, wenn es vom Unternehmen in die generelle Organisation, Ressourcenmanagement, Produktivität, Profit und Innovationen integriert wird, da dieseFaktoren am besten den Einfluß von ISO 9000 zeigen.
Keywords: 650